JALAN RAYA SEBAGAI DESAIN KEBUDAYAAN - Acep Iwan Saidi (Fakultas Seni Rupa dan Desain ITB, 2010)
This paper contains a brief analysis of the road, starting from the path to a modern highway. The analysis was performed in the cultural perspective. It means that the road is not seen as merely physical infrastructure of buildings, but how it constructs a network of knowledge and behavior of the cultures in it. Through this brief review, it is noted that the roads in its history experienced the shift function and meaning. For example, the functions of road that used to bring together both physical and nonphysical, but in its development, it actually has the function to work away. In the most recent phenomenon, road is also synonymous with